Cytokine Concentrations in Plasma from Children with Severe and Non-Severe Community Acquired Pneumonia - Haugen, Johanne; Chandyo, Ram K.; Brokstad, Karl A.; Mathisen, Maria; Ulak, Manjeswori; Basnet, Sudha; Valentiner-Branth, Palle; Strand, Tor A. (PLOS ONE, 2015)
Background Children in low and middle-income countries have a high burden of pneumonia. Measuring the cytokine responses may be useful to identify novel markers for diagnosing, monitoring, and treating pneumonia. Objective To describe and compare a wide range of inflammatory mediators in plasma from children with WHO-defined severe and non-severe community acquired pneumonia (CAP), and explore to what extent certain mediators are associated with severity and viral detection. Methods We collected blood samples from 430 children with severe (n = 43) and non-severe (n = 387) CAP. Plasma from these children were analysed for 27 different cytokines, and we measured the association with age, disease severity and viral detection. Results There were generally higher plasma concentrations of several cytokines with both pro-inflammatory and anti-inflammatory effects among children with severe CAP than in children with non-severe CAP. We found significantly higher concentrations of interleukin (IL)-1, IL-4, IL-6, IL-8, IL-9, IL-15, eotaxin, basic fibroblast growth factor (b-FGF), granulocyte colony-stimulating factor (G-CSF), granulocyte-macrophage colony-stimulating factor (GM-CSF), and tumor necrosis factor-alpha (TNF-α) in the group of severe CAP. Most of these associations persisted when adjusting for age in linear regression analyses. The cytokine response was strongly associated with age but to a lesser extent with viral etiology. Conclusion The plasma concentrations of several cytokines, both with pro-inflammatory and anti-inflammatory effects, were higher among children with severe illness. In particular G-CSF and IL-6 reflected severity and might provide complementary information on the severity of the infection. Trial registration ClinicalTrials.gov NCT00148733